Ethnozoological Knowledge and Family Economics on Attitudes and Behavior in Using Turtles - Dwi Setyawan; Syahrul Gunawan; Ainur Rofieq; Wahyu Prihanta; Fendy Hardian Permana (International Journal of Marine Engineering Innovation and Research, 2024)
The mutual interaction between humans and animals in the field of ethnozoology includes uses that can be oriented toward conservation or exploitation efforts. However, excessive abuse of sea turtles (Chelonioidea), especially in the direction of exploitation, has led to population decline and threatened their extinction. Observations in the Derawan Island community, Berau Regency, show a decrease in the number of turtles coming to lay their eggs due to overexploitation. To overcome this problem, it is necessary to carry out research that looks for factors that influence attitudes and behavior in using turtles, including the level of ethnozoological knowledge and family economic status. This research uses a quantitative approach with an analytical correlational design and applies Path Analysis. The results of the analysis show that the level of ethnozoological knowledge has a significant influence on attitudes, with a path coefficient of 0.298 in block-1. In block-2, the results of the analysis show that the level of ethnozoological knowledge directly influences turtle utilization behavior with a path coefficient of 0.313. In conclusion, the level of ethnozoological knowledge has a dominant role in shaping turtle utilization behavior in Derawan Island.